STRATEGI PEMASARAN USAHA NICE BAKERY DI TONDANO - Fitri Cahya Latif; Charles R. Ngangi; Celcius . Talumingan; Yolanda P. I. Rori (Universitas Sam Ratulangi, 2013)
AbstrakResearch to determine marketing strategies businesses Nice Bakery in Tondano. This study were obtained from the primary data, primary data source is taken through observation and interviews in respondents (businesses). Methods of data analysis in this study is a descriptive analysis of the marketing mix using SWOT analysis.Vased on the analysis of the matrix of Internal Extenal, Nice Bakery in the position of the vell V. where seen than Nice Bakery are at internal and external medium are also. Cell V is a group of cells with cell III and VII. Nice Bakery can be described on the defensive and achievement (hold and maintain) the strategy adopted include and intensive strategy (Penetration of market and product development). From the analysis has been done to implement the right strategy is market penetration and product development.The conclusion of the research that marketing strategy Nice Bakery business Product blased on quality, Price based on cost price and consumer expectation, promotion based on technology, facility distribution to make consumer easily to get Nice Bakery product and make partnership with food company and expand network by using technology.